Perspectives on music and evolution - Lüdemann, Winfried A. (HTS teologiese studies, 2022)
Many scholars of philosophy, aesthetics, religion, history or social science have ventured to offer a comprehensive explanation of music, one of the most intangible and elusive phenomena in the world. A palaeoanthropological approach, which places music into an evolutionary paradigm, can add important perspectives to our understanding of this phenomenon. To begin with, the question whether music is an adaptation that has survival value in the classical Darwinian sense is contemplated. Views on the origin of music in conjunction with the emergence of language and as a domain for the expression of emotion, linked to music’s benefits for social coherence, are discussed. More recent views on the emergence of consciousness, on semiosis and on music as a manifestation of biocultural co-evolution, especially in conjunction with ritual, are then presented. Finally, the merit of exploiting the concept of play to help account for the systematicity of music’s semiosis is examined.Contribution: In line with the intent of this special collection of articles, the above considerations are placed into the context of materialist versus nonmaterialist perspectives on the emergence of the human mind. The overarching argument is that music contributes crucially to what it means to be human.